2022
DOI: 10.1039/d1tb02709c
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose as a potential biopolymer in biomedical applications: a state-of-the-art review

Abstract: Natural biomaterials have favored human society for ages. Nevertheless, in late years, the tailoring of natural materials for diverse biomedical applications has turned into a core of attention, quarterbacked via...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 388 publications
0
21
0
Order By: Relevance
“…This finding was consistent to the results of Seto et al [ 37 ], which conjectured that the improved synthesis of BC may be observed in the process of cellulose fibers assembly in a co-culture system of Gluconacetobacter xylinus and Lactobacillus mali . Such a BC membrane has a great application prospect in not only the textile industry due to the increased comfort and dyeing characteristics of textiles, but also in the development of medical materials, such as artificial skin and wound dressing [ 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding was consistent to the results of Seto et al [ 37 ], which conjectured that the improved synthesis of BC may be observed in the process of cellulose fibers assembly in a co-culture system of Gluconacetobacter xylinus and Lactobacillus mali . Such a BC membrane has a great application prospect in not only the textile industry due to the increased comfort and dyeing characteristics of textiles, but also in the development of medical materials, such as artificial skin and wound dressing [ 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…coli (ATCC 25922). Equation is employed to evaluate the bacterial reduction ( R %) normalB normala normalc normalt normale normalr normali normala normall .25em normalr normale normald normalu normalc normalt normali normalo normaln ( R % ) = false( A B false) A × 100 where A is the number of bacterial colonies of the blank sample and B is the number of bacterial colonies of the thermochromic sample, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of hydrogels as functional biomaterials in biomedical applications started in the early 19th century [ 1 , 2 ]. As per the report by Wichterle and Lim, hydrogel was initially used in biomedical applications as tissue scaffolds and contact lenses, but later, in the early 20th century, it was also used as high aqueous-swellable crosslinked polymeric networks [ 3 ].…”
Section: Introductionmentioning
confidence: 99%